(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The idea of identity is fundamental fold, hard to characterize and sidesteps many customary techniques for measurement. The twentieth century driving researcher of Identity, Erik Erikson, named the idea of all – pervasive yet additionally vague and unfathomable identity. The rankling unavoidability of identity is very much shown in crafted by the recognized social scholar Leon Wieseltier. Identities are imperative since they shape the conduct of individuals. Both individual and group have identities. People, in any case, adjust their identities in groups. As social identity hypothesis has appeared, the requirement for identity drives them even to look for identity in a subjectively and randomly developed group. In India, feminism has been less of an ism and to a greater extent a social movement. It has a background marked by its own. Amid the Vedic time frame, woman appreciated a favored position and status practically equivalent to that of man. In any case, amid the sixties and the seventies of the present century, a feminine revolt occurred the world over and it reprimanded all burdens on women in a patriarchal setup. Women, who were imprisoned by convention, began to view her from an alternate edge and understood her own self. Rather than being formed into the conventional picture managed by the society, she has taken the shape that mirrors her true self. In this Article, we analyzed Quest of Identity and Prominent Women Feminist Writers in India.